2018
DOI: 10.1111/crj.12948
|View full text |Cite
|
Sign up to set email alerts
|

Chronic opioid use and clinical outcomes in lung transplant recipients: A single‐center cohort study

Abstract: This analysis presents the first evidence that late-onset chronic opioid use may be associated with decreased lung function and increased mortality after LTx. Therefore, evaluation of chronic opioid use should be included in the routine monitoring of transplant recipients, to better define the impact of this risk factor on LTx outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A second study of 70 942 adolescents and young adults who were opioid-naive (70% ≤18 years old) found that a filled perioperative opioid prescription after wisdom tooth extraction was associated with 2.7 higher odds of persistent opioid use compared with those who did not fill an opioid prescription after extraction . Additional studies assessing development of long-term opioid use after surgery are limited to specific diagnoses limiting generalization …”
Section: Resultsmentioning
confidence: 99%
“…A second study of 70 942 adolescents and young adults who were opioid-naive (70% ≤18 years old) found that a filled perioperative opioid prescription after wisdom tooth extraction was associated with 2.7 higher odds of persistent opioid use compared with those who did not fill an opioid prescription after extraction . Additional studies assessing development of long-term opioid use after surgery are limited to specific diagnoses limiting generalization …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other studies have reported a 30-50% rate of discharge with opioids, suggesting a potential benefit to adjunct therapies in reducing the duration of acute post-thoracotomy pain and the need for further opioids. 10,23,24 Lastly, patients treated with this protocol had a relatively short duration of stay in the ICU and hospital (10 days vs. median 18 days nationally or 16 days for UNOS Region 9) and similar readmission rates (36% vs. 33-45% in other cohorts). [25][26][27] The effect of adjunctive analgesics on PTPS remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…However, the low daily opioid dose may have limited the ability to detect a difference, as outcomes have historically been worse in heavy opioid users 8,9 . In contrast, post lung transplant opioid dependence has been linked with increased mortality and worse lung function, and many patients remain on opioids chronically 10,19 . These studies highlight the need to carefully screen for opioid use pre‐transplant and also to minimize opioid use post‐transplant to avoid any negative effects on graft and patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations